Thermally activated delayed fluorescence materials based on benzophenone derivative as emitter for efficient solution-processed non-doped green OLED. (October 2016) - Huang, Bin; Ban, Xinxin; Sun, Kaiyong; Ma, Zhongming; Mei, Yanan; Jiang, Wei; Lin, Baoping; Sun, Yueming
Abstract: A series of thermally activated delayed fluorescence materials based on benzophenone derivatives have been synthesized by Ullmann coupling reaction. The optical, electrochemical and thermal properties of benzophenone derivatives were systematically characterized. In comparison with the reported thermally activated delayed fluorescence materials based on benzophenone derivatives, bis-4-[3, 6-bis(3, 6-di- tert -butyl-carbazol-9-yl)carbazol]-9-yl-phenyl-methanone exhibited better solubility and smaller energy gap between the singlet and triplet excited states (0.08 eV). The solution-processed non-doped green OLED using this novel material as an emitter exhibited a low turn-on voltage of 4.5 V, a maximum current efficiency of 9.2 cd A −1, a high external quantum efficiency of 4.3%, and a maximum luminance of 4200 cd m −2 . Graphical abstract: Highlights: Benzophenone derivatives for delayed fluorescence have been synthesized. The optical, electrochemical and thermal properties were studied. The solution-processed non-doped green OLEDs exhibited a high EQE of 4.3%.